An approach to support the Knowledge Management Process inside professional activities. (1st December 2008) - Monticolo, Davy; Gomes, Samuel; Hilaire, Vincent; Koukam, Abder
This article proposes an approach to model, identify, synthesise and reuse knowledge all along engineering design projects. As a matter of fact, these projects require that engineers, with different specialities, collaborate to carry out the same goal. Inside professional processes, they use their know-how and knowledge to achieve the laid down goals. Our approach consists in using an organisational approach to identify the competences and knowledge of professional actors which allows the design and the description of agents' know-how. Furthermore, the article describes the design of our agent model based on an organisational approach and the role of a domain-ontology called OntoDesign to manage heterogeneous and distributed knowledge.